The Role of HR in Driving Organizational Sustainability through Employee Well Being Programs - Dyageti, Sandya Rani; Uday Kiran, K.C. (International Journal of Advances in Business and Management Research (IJABMR), 2025)
In the evolving landscape of corporate responsibility, the role of Human Resources (HR) in promoting organizational sustainability has gained significant attention. This paper explores how HR functions can be strategically aligned with sustainability goals through the implementation of employee well-being programs. These programs—ranging from mental health support and flexible work arrangements to ergonomic workspaces and green commuting incentives—serve as vital tools not only for enhancing employee satisfaction and productivity but also for contributing to broader environmental and social objectives. A sustainable organization recognises its workforce as a critical stakeholder in achieving long-term goals. By integrating well-being initiatives into corporate sustainability strategies, HR can foster a culture of health, resilience, and inclusivity. This paper examines real-world case studies and surveys to demonstrate that organizations investing in holistic well-being report improved employee retention, enhanced brand reputation, and greater compliance with Environmental, Social, and Governance (ESG) standards. Moreover, the study highlights the feedback loop between sustainable HR practices and business performance, indicating that employee-centric sustainability initiatives often lead to greater innovation and reduced operational risks. The research underscores the importance of reimagining HR not merely as an administrative function, but as a proactive driver of sustainable transformation. Ultimately, the paper advocates for a shift in HR strategy—from reactive support to strategic leadership—emphasising the need for continuous measurement, employee involvement, and alignment with global sustainability frameworks such as the UN Sustainable Development Goals (SDGs).